Carte de Brest - ca 1700 - Bibliothèque Nationale de France - Btv1b8439976x - Bibliothèque nationale... (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons. Titre: Carte de Brest - ca 1700 - Bibliothèque Nationale de France - Btv1b8439976x. Title: Brest, city of France in Lower Brittany with one of the Kingdom's largest ports in a large bay. Handwritten cartographic material of the city of Brest and fortifications.
Droits : Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons; Iconographie